Molecular Detection of Lumpy Skin Disease in Cattle Samples (Bos taurus) at Lampung Disease Investigation Center - Yunior, Elfita Nova; Rustiati, Elly Lestari; Srihanto, Eko Agus; Firwantoni, Firwantoni; Heni, Ahyul; Panasea Anggy, Fransiska; Febriyani, Dwi Ayu (Jurnal Agrosci, 2025)
Lumpy Skin Disaese, LSD, was first discovered in Indonesia in Riau Province in February 2022. Although LSD is not a zoonotic disease, its infection can affect the production and reproductive performance of cattle, resulting in various impacts including reduced milk production, weight loss, miscarriages, and infertility as well as significant economic losses. It is a vector-borne smallpox disease of cattle and buffalo. Characterized by the appearance of pustules on the skin. Identification of LSDV can be carried out by three methods, namely Polymerase Chain Reaction (PCR), virus isolation, and electron microscopy. PCR is the cheapest and fastest method to detect LSDV. LSD disease testing at the Biotechnology Laboratory, Lampung Disease Investigation Center using the RT- PCR method. No LSD was found over 13 blood samples and 2 nasal swab samples from January 2024 sampling showed that all of them were negative to LSD.